THE EFFECT OF DIGITAL COMICS LEARNING MEDIA IN IMPROVING STUDENTS' LITERACY - Putri Dewi Anggraeni (Jurnal Profesi Keguruan, 2024)
Reading is one of the skills that students must have. Students who don't like reading could have a bad impact on other people. For educators, increasing interest in reading is a struggle. Basically, because the material that students read is only printed books full of writing, their interest in reading becomes less. More impressive media is needed to arouse elementary school students' interest in reading. Students become engaged during reading when they discover charming illustrations and various writing fonts in books. Instructors must be more creative in creating reading materials for their students. For example, they might create digital comic learning materials that provide a different reading aesthetic than traditional books. This research takes a closer look at how innovation modifies conventional comic-based learning media into digital comics because the learning material delivered and interspersed with digital comic media can attract students' attention and trigger their passion for reading. This kind of research uses qualitative literature study techniques. The main source of information is in library